The history and present of the inter-cooperation network – the study of The New Hanseatic League and The Lusatian League - Przybyła, Zbigniew (Economics, 2011)
The towns belonging to so called The New Hanseatic League and The Lusatian League represent networks of twinned towns. Their specificity is the historic nature of the relationships initiated during the Middle Ages and after a long break, resumed at the end of the last millennium. In this article similarities and differences between these groups are analyzed on the background of characteristics of both compounds
Ekonomia = Economics, 2011, Nr 5 (17), s. 249-257
Keywords: international co-operation of local government; a network of partner cities; The New Hanseatic League; The Lusatian League; współpraca międzynarodowa samorządów lokalnych; sieć miast partnerskich; nowa Hanza; Związek Miast Łużyckich